The Fall of an Imperial Ambassador: Count Georg Adam von Martinitz and His Recall from Rome (Theatrum historiae, 2017)
The paper discusses the changes in the diplomatic relations between Rome and Vienna during the embassy tenure of Count Georg Adam von Martinitz (1696–1700). The series of his conflicts with the Holy See (e.g., the scandal at the Corpus Christi procession, the affairs of the imperial feuds in Italy and finally a poisoning attempt) deteriorated his situation at the Roman Curia. That resulted in his being denied Papal audiences and the recall of Martinitz from Rome. But it should have been anticipated by his relatives in Vienna. Martinitz received another Imperial Court posting, although he was not satisfied with it. Although he inherited most of these conflicts, he was not able to dissolve them; in fact, he made some of them worse. His successor, Count Leopold Joseph von Lamberg, arrived to Rome with the task “to put water on the fire”. But it was not an easy task, especially on the eve of the War of the Spanish Succession.
Keywords: Habsburg; diplomacy; Rome; Papal Court; Martinitz